An outbreak investigation of scrub typhus in Western Province, Solomon Islands, 2014 - Marks, Michael; Joshua, Cynthia; Longbottom, Jenny; Longbottom, Katherine; Sio, Alison; Puiahi, Elliot; Jilini, Greg; Stenos, John; Dalipanda, Tenneth; Musto, Jennie (Western Pacific Surveillance and Response, 2016)
Objective: To identify the etiology and risk factors of undifferentiated fever in a cluster of patients in Western Province, Solomon Islands, May 2014. Methods: An outbreak investigation with a case control study was conducted. A case was defined as an inpatient in one hospital in Western Province, Solomon Islands with high fever (> 38.5 °C) and a negative malaria microscopy test admitted between 1 and 31 May 2014. Asymptomatic controls matched with the cases residentially were recruited in a ratio of 1:2. Serum samples from the subjects were tested for rickettsial infections using indirect micro-immunofluorescence assay. Results: Nine cases met the outbreak case definition. All cases were male. An eschar was noted in five cases (55%), and one developed pneumonitis. We did not identify any environmental factors associated with illness. Serum samples of all five follow-up cases (100%) had strong-positive IgG responses to scrub typhus. Nine out of ten controls were negative for ST antibodies. Four controls had low levels of antibodies against spotted fever group rickettsia, and only one had a low-level response to typhus group rickettsia. Discussion: This outbreak represents the first laboratory-confirmed outbreak of scrub typhus in the Western Province of Solomon Islands. The results suggest that rickettsial infections are more common than currently recognized as a cause of an acute febrile illness. A revised clinical case definition for rickettsial infections and treatment guidelines were developed and shared with provincial health staff for better surveillance and response to future outbreaks of a similar kind.